PENGARUH KECERDASAN EMOSIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Panji Pramuditha S.Sos, M.M (ATRABIS: Jurnal Administrasi Bisnis (e-Journal), 2017)
Abstract The aim of this study is examine the impact between emotional intelligence and job satisfaction to job performance. This study is using survey from PT Bank BII Maybank Indonesia Tbk Secured Loan division Asia Afrika Bandung, and used 64 people from secured loan division as respondent. Also, all data can be used. The outliers, validity, reliability, descriptive statistics and verificative statistics tests were conducted before hypothesis was tested. The linier regression analysis was used to examine the hypothesis.The result shows that emotional intelligence and job satisfaction have impact to job performance in PT Bank BII Maybank Indonesia Tbk Secured Loan Division Asia Afrika Bandung of 63.84%, while the rest 36.16 % influenced by other variable. Based on the results of studies there are some advice to improve employee performance .The emotional intelligence be better if focus to motivate employees and do morning breafing. Gave directions in the point of view of customers. Clear the rewards and pusnishment to increase again variable satisfaction work.